Implementasi Metode Two Stay Two Stray Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran SKI Kelas XI Man 2 Langkat - Intan Sari Siregar, Kamaliah R, Ahmad Zaki (LPPPI Publishing, 2022)
This aims to determine how the implementation of the two stay two stray method to improve student learning outcomes in class XI MAN 2 Langkat. This research is a qualitative research, data collection is done by conducting interviews, observations or observations and documentation. The examination of the validity of the data was carried out by conducting data triangulation, namely comparing data from direct observations with data from interviews with educators and related documentation. The results showed that the learning process using the two stay two stray method had been going well. The teacher’s role as a motivator, facilitator and organizer has been maximized. This means that the learning achievement goals are in line with expectations, according to the title of this thesis, namely the implementation of the two stay two stray method to improve student learning outcomes in class XI MAN 2 Langkat.